Model Strategi Pengembangan Sistem Informasi Manajemen Pendidikan (SIMDIK) Berbasis Website - Laely Nurhayati; Retno Purwaningsih (CV. ITTC INDONESIA, 2026)
The advancement of information technology demands that educational institutions shift from manual management to an integrated and efficient system. This paper examines a strategic model for developing a website-based Education Management Information System (SIMDIK) as a solution for education management in the digital era, using a literature review approach based on management information theory, national education regulations, and the implementation of digital education system reports. The study reveals six main strategies for developing SIMDIK: administrative digitization, academic service integration, data-driven decision-making, stakeholder service enhancement, digital culture development, and integration with national systems such as DAPODIK. Implementing these strategies can improve administrative efficiency, data accuracy, governance transparency, and the quality of education services. Website-based SIMDIK is a strategic foundation for realizing modern, accountable education management that is oriented toward continuous quality improvement.